TILNI O'QITISHDA ZAMONAVIY METODLARNING O'RNI («MODERN PHILOLOGICAL PARADIGMS: INTERACTION OF TRADITIONS AND INNOVATIONS», 2025)
This article explores the place of modern methods in teaching foreign languages.Literature analysis and the study of practical experiments have been used as research methods.The results show that modern methods make language learning an effective and interesting process. The analysis and discussion will consider the advantages and disadvantages of these methods. The conclusion provides recommendations for the introduction of modern methods.